Personality systems interactions theory: an integrative framework complementing the study of the motivational and volitional dynamics underlying adjustment to chronic pain - Kästner, Anne; Petzke, Frank (Frontiers in Pain Research, 2024)
In the endeavor to advance our understanding of interindividual differences in dealing with chronic pain, numerous motivational theories have been invoked in the past decade. As they focus on relevant, yet different aspects of the dynamic, multilevel processes involved in human voluntary action control, research findings seem fragmented and inconsistent. Here we present Personality Systems Interactions theory as an integrative meta-framework elucidating how different motivational and volitional processes work in concert under varying contextual conditions. PSI theory explains experience and behavior by the relative activation of four cognitive systems that take over different psychological functions during goal pursuit. In this way, it may complement existing content-related explanations of clinical phenomena by introducing a functional, third-person perspective on flexible goal management, pain acceptance and goal maintenance despite pain. In line with emerging evidence on the central role of emotion regulation in chronic pain, PSI theory delineates how the selfregulation of positive and negative affect impacts whether behavior is determined by rigid stimulusresponse associations (i.e., habits) or by more abstract motives and values which afford more behavioral flexibility. Along with testable hypotheses, multimodal interventions expected to address intuitive emotion regulation as a central process mediating successful adaptation to chronic pain are discussed.